Design Basis of Movable Scaffolding Systems Following American and European Code Provisions and Recommendations - Marck Anthony Mora Quispe; Leonardo Todisco; Hugo Corres Peiretti (The Baltic Journal of Road and Bridge Engineering)
Construction of bridges span-by-span with Movable Scaffolding Systems (MSSs) is a very efficient and competitive technology. Normally used for spans between 25 and 70m, the technology has allowed reaching longer spans due to technological advances, specifically in bridge construction equipment. Thereby, the use of MSS has become widespread and well-accepted in a large number of locations across the USA and Europe. Nevertheless, despite its extended application, there is no single specific code provision that can explain, control, and give recommendations about all aspects of MSS during its design and usage. On the contrary, the information is spread over several documents. This paper aims at bridging this gap by providing an extensive review of code provisions and recommendations that can be valid for the MSS design. Applicability of these documents is discussed by analysing loads, safety factors, load combinations, limit states, as well as structural analysis and design. After this, a proposal of a design basis for MSS is presented for each aspect mentioned following provisions and recommendations of the considered codes.